Affordable Small Molecules as Promising Fluorescent Labels for Biomolecules - Raquel Eustáquio; João P. Prates Ramalho; Sílvia Arantes; António Candeias; Ana Teresa Caldeira; António Pereira (Molecules)
Fluorescent labels, commonly used in highly sensitive analytical techniques for detecting and tracking biomolecules in critical fields like cellular biology, medicine, medicinal chemistry, and environmental science, are currently too expensive for routine use in standard applications, with most exhibiting small Stokes shifts. This limitation underscores the potential of 4-diethylaminobenzaldehyde derivatives as a cost-effective alternative for developing new, bright fluorophores with larger Stokes shifts. In this work, using 4-diethylaminobenzaldehyde as starting material, we developed a simple, cost-effective, and efficient synthetic strategy to produce new affordable small molecules as effective fluorescent labels for biomolecules. Density functional theory and time-dependent density functional theory calculations were also conducted to gain insights into the observed photophysical properties.